The Molecular Epidemiology and Evolution of Murray Valley Encephalitis Virus: Recent Emergence of Distinct Sub-lineages of the Dominant Genotype 1 - Williams, D.; Diviney, S.; Niazi, A.; Durr, P.; Chua, Beng Hooi; Herring, B.; Pyke, A.; Doggett, S.; Johansen, C.; Mackenzie, John (2015)
© 2015 Williams et al. Background: Recent increased activity of the mosquito-borne Murray Valley encephalitis virus (MVEV) in Australia has renewed concerns regarding its potential to spread and cause disease. Methodology/Principal Findings: To better understand the genetic relationships between earlier and more recent circulating strains, patterns of virus movement, as well as the molecular basis of MVEV evolution, complete pre-membrane (prM) and Envelope (Env) genes were sequenced from sixty-six MVEV strains from different regions of the Australasian region, isolated over a sixty year period (1951–2011). Phylogenetic analyses indicated that, of the four recognized genotypes, only G1 and G2 are contemporary. G1 viruses were dominant over the sampling period and found across the known geographic range of MVEV. Two distinct sub-lineages of G1 were observed (1A and 1B). Although G1B strains have been isolated from across mainland Australia, Australian G1A strains have not been detected outside northwest Australia. Similarly, G2 is comprised of only Western Australian isolates from mosquitoes, suggesting G1B and G2 viruses have geographic or ecological restrictions. No evidence of recombination was found and a single amino acid substitution in the Env protein (S332G) was found to be under positive selection, while several others were found to be under directional evolution. Evolutionary analyses indicated that extant genotypes of MVEV began to diverge from a common ancestor approximately 200 years ago. G2 was the first genotype to diverge, followed by G3 and G4, and finally G1, from which subtypes G1A and G1B diverged between 1964 and 1994. Conclusions/Significance: The results of this study provides new insights into the genetic diversity and evolution of MVEV. The demonstration of co-circulation of all contemporary genetic lineages of MVEV in northwestern Australia, supports the contention that this region is the enzootic focus for this virus.